(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, information about the work of Shukur Kholmirzayev, his works, stories, creative heritage were touched upon. The work of his contemporaries thoughts about his work, his place in literature, a comment on the study of his work is conducted.